Analisis Faktor Terjadinya Kecanduan Game di Indonesia - Herman, Daniel Apdianto (Universitas Internasional Batam, 2019)
Online Gaming is a world phenomenon, include in Indonesia. Online Game Addiction is a worrying condition. The main factor about why the online game is having a large fanbase until addiction case happens, especially in Indonesia, is not studied formally. This research found out the factors in Indonesia is exrensive and intertwined, but the main factor is gamer in Indonesia that are not mature enough.